1798 Md. Laws ch. C, § XXIII - (:unkn) unknown (My University, 1798)
Required that "one complete company of infantry annexed to each regiment within this state, to be furnished with arms and accoutrements at the expense of the state ? composed of men between the ages of twenty-one and thirty years."
Keywords: MILITIAS